Love, Ruby Lavender - Wiles, Deborah (New York Harcourt, Inc., 2001)
When her quirky grandmother goes to Hawaii for the summer, nine-year-old Ruby learns to survive on her own in Missippi by writing letters, befriending chickens as well as the new girl in town, and finally coping with her grandfather's death.
5 - 9
Keywords: Grandparents - Fiction; Self-reliance - Fiction; Death - Fiction; Missippi - Fiction